Feasibility and impact of Muara Bulian Bridge construction on the economy of Batang Hari Regency - Muhammad Safri (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2017)
This study aims to determine the impact of Muara Bulian bridge construction on the economy of Batang Hari Regency. The number of vehicles transporting goods (transport coal and CPO) through the City of Muara Bulian has made congestion in the City of Muara Bulian. Therefore, it takes a diversion of currents for freight vehicles sothey will not cross the city of Muara Bulian. The scope of the research focused on the social and economic impacts of the bridge construction and the feasibility study of the bridge financially. The type of data used is the type of secondary data obtained from interviews and data from related agencies in Jambi Province and Batang Hari Regency in 2016. Based on the results of the research, it is found that: (1) Construction of Muara Bulian Bridge is intended to build isolated areas in the Maro Sebo Ilir Subdistrict. Maro Sebo Ilir Subdistrict has enormous potential in terms of both plantations and mining. Potential plantations in Maro Sebo Ilir Subdistrict are oil palm and rubber while for mining there is coal and oil. The construction of the Muara Bulian bridge is expected to create new economic growth centers in Batang Hari Regency and can increase the strength and opportunities of new business potentials that have not existed in Batang Hari Regency, and (2) road connectivity on the north of the Muara Bulian bridge will be connected to an existing provincial road. To facilitate the flow of transportation to the provincial road, it is necessary to create a new road along ± 3 km with an estimated cost of ± Rp. 8,400,000,000 with standard cost 2,800,000,000 /km. Keywords: Financial feasibility, regional economy, socio-economic impact